2020
DOI: 10.3390/biom10111575
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol: A Potential New Alternative for the Treatment of Anxiety, Depression, and Psychotic Disorders

Abstract: The potential therapeutic use of some Cannabis sativa plant compounds has been attracting great interest, especially for managing neuropsychiatric disorders due to the relative lack of efficacy of the current treatments. Numerous studies have been carried out using the main phytocannabinoids, tetrahydrocannabinol (THC) and cannabidiol (CBD). CBD displays an interesting pharmacological profile without the potential for becoming a drug of abuse, unlike THC. In this review, we focused on the anxiolytic, antidepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
134
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(148 citation statements)
references
References 204 publications
(253 reference statements)
5
134
0
9
Order By: Relevance
“…Due to its minimal toxicity in humans, an interesting number of trials have been performed to determine the clinical efficacy of CBD in different pathologies. Numerous CBD formulations have been assessed in preclinical studies for various pharmaceutical properties, such as anti-nausea, anti-emetic, anti-tumor, anti-inflammatory, antidepressant, anti-psychotic, and anti-anxiolytic [ 10 , 11 , 12 , 99 ] benefits. Nevertheless, the variation in CBD quality, the type of drug formulations applied, and the minimal sample sizes compromise the development of these preclinical studies.…”
Section: Clinical Trials Of Cannabidiol Focused On Demyelinating Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its minimal toxicity in humans, an interesting number of trials have been performed to determine the clinical efficacy of CBD in different pathologies. Numerous CBD formulations have been assessed in preclinical studies for various pharmaceutical properties, such as anti-nausea, anti-emetic, anti-tumor, anti-inflammatory, antidepressant, anti-psychotic, and anti-anxiolytic [ 10 , 11 , 12 , 99 ] benefits. Nevertheless, the variation in CBD quality, the type of drug formulations applied, and the minimal sample sizes compromise the development of these preclinical studies.…”
Section: Clinical Trials Of Cannabidiol Focused On Demyelinating Dmentioning
confidence: 99%
“…Considerable interest in CBD is emerging due to its beneficial antiepileptic [ 8 ], neuroprotective in hypoxia-ischemia [ 9 ], anxiolytic, antipsychotic [ 10 ], anti-inflammatory [ 11 ] and anticancer properties [ 12 ], among others ( Table 1 ). In the past, CBD has received less attention as a potential drug candidate than Δ9-THC although it has been commonly used in cannabis-based formulations.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a study comparing different doses of nabiximols to placebo found out that the use of a high dose (11-14 sprays/day) exacerbated depression (119), reinforcing the signal that higher doses of cannabinoids may be prodepressogenic. In contrast, early data from pre-clinical studies of CBD are suggestive of possible antidepressant effects (125)(126)(127)(128)(129). We are unaware of any randomized controlled trial investigating nabilone (synthetic orally administered THC compound) or CBD in the treatment of MDD.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Human studies confirmed that CBD is well-tolerated by patients at both low and high doses, even up to 1500 mg/day, and its administration, both acute and chronic, does not cause any significant changes in central nervous system functionality. However, it has been shown that this compound may have immunosuppressive properties due to its reductive effect on Interleukin-8 and -10 biosynthesis as well as the possibility of lymphocyte apoptosis induction [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%